2017
DOI: 10.1038/cddis.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cell death is regulated by TNF-α-induced expression of B-cell activating factor through an ERK-dependent increase in hypoxia-inducible factor-1α

Abstract: B-cell activating factor (BAFF) has a role in the maturation and maintenance of B cells and is associated with rheumatoid arthritis (RA). Here, we investigated whether tumor necrosis factor (TNF)-α-induced BAFF expression controls the survival of fibroblast-like synoviocytes (FLS) and whether their survival can be regulated by TNF-α-mediated upregulation of hypoxia-inducible factor (HIF)-1α using MH7A synovial cells transfected with the SV40 T antigen. More TNF-α-treated cells died compared with the control. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…4 C ). On the other hand, by using primary chondrocytes from Col2a1‐CreER T2 ; Ezh2 f/f mice, we confirmed the decrease of Tnfsf13b in Ezh2 knockout chondrocytes (Fig. D , Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…4 C ). On the other hand, by using primary chondrocytes from Col2a1‐CreER T2 ; Ezh2 f/f mice, we confirmed the decrease of Tnfsf13b in Ezh2 knockout chondrocytes (Fig. D , Supplementary Fig.…”
Section: Resultssupporting
confidence: 56%
“…BAFF expression is regulated by various signaling pathways, including the activation of JAK/STAT ( Woo et al ., 2013 ), CREB-binding protein/p300 ( Moon and Park, 2007 ), lipopolysaccharide (LPS)-induced protein kinase A-mediated CREB, Epac1-mediated Rap1 ( Moon et al ., 2011a , 2011b), nuclear factor-kappa B by LPS-induced production of reactive oxygen species (ROS) ( Moon et al ., 2006 ), and ROS-dependent protein kinase C (PKC)/c-Fos pathways. ERK pathways are also involved in TNF-α-induced BAFF expression in FLS ( Lee et al ., 2017 ). Our data show that BAFF expression by TNF-α could be associated with the activation of kinase (JNK, p38 and ERK) and transcription factors (p65, CREB, c-Fos and SP1) in FLS.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α-stimulated FLS express B-cell activating factor (BAFF), originally known as a B-cell proliferation and survival factor ( Mackay and Kalled, 2002 ; Lee et al ., 2017 ). BAFF is produced by immune cells (monocytes, dendritic cells, and macrophages) ( Mackay and Browning, 2002 ), and also by non-immune cells, such as salivary gland epithelial cells ( Ittah et al ., 2008 ), prostate epithelium ( Di Carlo et al ., 2009 ), and FLS ( Ohata et al ., 2005 ; Lee et al ., 2017 ). Excess levels of BAFF are detected in patients with an autoimmune disease, and particularly in the synovial tissue of patients with RA ( Nakajima et al ., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence demonstrates that hypoxia inducible factor-1α (HIF-1α) is the main upstream inducer of VEGFA, which plays a key role in tumor angiogenesis [ 36 , 37 ]. Recent studies have characterized a series of HIF-1α related pathways, such as the ERK [ 38 ], TNF-α [ 39 ], phosphatidylinositol-3-kinase (PI3K), mammalian homologue target of rapamycin (mTOR), and AKT [ 40 , 41 ] pathways. Here, we found that UBE2CP3 up-regulated the levels of p-ERK, phosphor-p70S6K (p-p70S6K), HIF-1α, and VEGFA in HCC cells.…”
Section: Discussionmentioning
confidence: 99%